THE IMPACT OF EXTENSIVE READING TECHNIQUE ON THE STUDENTS’ VOCABULARY MASTERY AT THE EIGHT GRADE OF SMPN2 KUALUH SELATAN: DAMPAK TEKNIK MEMBACA EKSTENSIF TERHADAP PENGUASAAN KOSA KATA SISWA DI DELAPAN KELAS SMPN 2 KUALUH SELATAN - Lovita Damanik, Dea (UPMI Proceeding Series, 2024)
The reasearch entitled The Impact Of Extensive Reading Technique On The Students’ Vocabulary Mastery At The Eight Grade Of Smpn2 Kualuh Selatan. With the main problem studied in this research, namely what is the impact of extensive reading on students’ in vocabulary mastery at Smpn2 Kualuh Selatan. This research aim to find out whether the use of extensive reading has an impact or not on students’ vocabulary mastery. The researcher used a pre- experimental one group pre-test and post-test design, which consisted of six meetings including the treatments. Population in this reasearch were the eight grade students of Smpn2 Kualuh Selatan consisted of 6 clases. The sample was used was a purposive sampling technique with a total of 40 students. The instrument of this research used multiple-choice tests to obtain the data. From the data obtained indicate that there was a changed in student test results. The avarage score of students taught usinng extensive readiing technique 77,25, The avarage score of students taught without using extensive reading technique 67,75.